Determination of Galendo’s Shelf Life on Various of Storage Temperatures by Arrhenius Method - Asep Dedy Sutrisno; Wisnu Cahyadi (International Journal of Science and Society, 2021)
This study aims to estimate the shelf life by applying the Arrhenius formula model to "galendo" which is vacuum packed and stored at various temperatures. Estimation of the shelf-life limit of galendos was carried out by measuring the peroxide number and sensory values ​​of galendos which were deliberately kept open without being packed at room temperature (25 ○C). The sensory values ​​used as the threshold for consumer rejection of the level of galendo's rancid odor were achieved on the 27th day of storage and the current peroxide count value was 42.2724 meq/kg. Galendo which was vacuum packed with aluminum foil and stored at various temperatures of 15 ○C, 25 ○C, and 35 ○C, then the shelf life was determined using the Arrhenius and Q10 models based on the parameters of the total peroxide number (TPN) and the total microbial content. Based on the experiment in this study, the estimation results of galendo's shelf life based on the total peroxide number (TPN) test parameter show that storage at 15 ○C has a shelf life of 83 days with a deterioration rate (k) of 0.0207, storage at 25 ○C shelf life 67 days with a deterioration rate (k) 0.0247, and storage at a temperature of 35 ○C for 58 days with a deterioration rate (k) 0.0286. The rate of quality degradation with a value of Q10 (15 oC - 25 oC) of 1.23 and a value of Q10 (25 oC - 35 oC) of 1.16. The higher the storage temperature, the higher the microorganism content.